Usability Testing of User Manuals - Møller, Margrethe H. (Communication & Language at Work, 2013)
Many guidelines and several standards exist for the development of good user manuals. But even though technical writers comply with all guidelines, problems will typically arise when users apply the manual in practice. Therefore, it is useful to have real users test the manual before it is published. This article discusses user tests in the form of think-aloud tests, with examples from the research project ”User Manuals for older adults”.